Thin-film heterostructures based on conducting polymers and organic semiconductors - Vertsimakha, Ya.I.; Aksimentyeva, O.I.; Perminov, R.J.; Poliovyi, D.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
We have carried out the experimental verification of a possibility to produce organic heterostructures by using films of organic semiconductors (OS) which are photosensitive in a wide spectral region, absorb light, and generate charge carriers in the region of transparency of films of conducting polymers – electrochemically synthesized polyaniline (PAN) and poly-3,4-ethylenedioxythiophene (PEDOT) stabilized by polystyrenesulfone acid (PSS). As components for the fabrication of these heterostuctures, we chose photosensitive organic semiconductors of the n-type, N,N`- dimethyl-3,4,9,10-perylenetetracarboxydiimide (МРР), and of the р-type, pentacene (Pn), which were thermally sprayed on thin layers of PAN and PEDOT. The photovoltage of heterostuctures produced at the temperature of substrates 370 K is several times greater than that of components, reaches its maximum in the region of strong light absorption in OS layers, but is one order less in the region of strong absorption in polymers. This testifies to the appearance of an internal electric field near the polymer/OS boundary which enhances the efficiency of separation of photogenerated charge carriers, whereas the efficiency inherent to photogeneration of carriers in the layers with PAN and PEDOT-PSS is insufficient yet.